“NEW NORMAL” OF POST-COVID AND POST-MODERN WORLD IN THE MIRROR OF THE LANGUAGE - Harutyunyan, Narine (Armenian Folia Anglistika, 2022)
Today humanity is going through a period of radical transformation of the world, the principles of the existence of society, economy, education, traditional values. We are witnessing giant shifts in world politics, epic battles between Good and Evil. It can be assumed that the modern society of the post-covid era is moving in the direction of "new postmodernism" and "post-capitalism". The world elite is trying to “recode” sociocultural reality, human existence, linguistic consciousness. With the help of new cultural concepts and linguistic signs, not only the “New Reality” is created and described, but also the “neology” of this reality. This article is a study of the actual problem of neologization, in the context of the above-mentioned dynamic processes occurring in the post-covid world. It is aimed at identifying and describing linguistic means reflecting the current trends of the world elite in establishing a "New World Order". To implement a "radical transformation" and to impose a "New World Order" with new values ​​and traditions, the "newspeak" of the post-pandemic era is used. The object of our research is new terms and concepts of the actual spheres of social life, as an important fragment of a new conceptual and linguistic picture of the world. Keywords: “social puppet”, neologization, New World Order, Great Reset, gender-neutral language, metamodernism,